2013
DOI: 10.1002/ijc.28544
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gastrointestinal events with sorafenib, sunitinib and pazopanib in patients with solid tumors: A systematic review and meta‐analysis of clinical trials

Abstract: Gastrointestinal (GI) events have been described with sorafenib, sunitinib and pazopanib in cancer patients. We performed an up-to-date meta-analysis to determine the incidence and relative risk (RR) in patients with cancer treated with these agents. PubMed databases were searched for articles published till May 2013. Eligible studies were selected according to PRISMA statement. Summary incidence, RR, and 95% CIs were calculated using random-effects or fixed-effects models based on the heterogeneity of selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Dyspepsia and related gastrointestinal disorders have been reported as adverse reactions following therapy with smTKIs [11,12,[150][151][152]. Treatment options are the use of antacids, histamine H2 receptor antagonists and proton pump inhibitors (PPIs) [149].…”
Section: Stomach Ph Regulating Drugsmentioning
confidence: 99%
“…Dyspepsia and related gastrointestinal disorders have been reported as adverse reactions following therapy with smTKIs [11,12,[150][151][152]. Treatment options are the use of antacids, histamine H2 receptor antagonists and proton pump inhibitors (PPIs) [149].…”
Section: Stomach Ph Regulating Drugsmentioning
confidence: 99%
“…Based on our results, these procedures utilized for a proper diagnosis of malnutrition have a high sensitivity for the detection of malnutrition and can rather easily be integrated into clinical routine. Certainly, nutritional therapy should be initiated to improve a patient's clinical state and quality of life and condition the patient for further treatments such as surgery, chemotherapy or some of the newly approved molecular targeted therapies which frequently are associated with some degree of weight loss [71,72,73,74]. The assumed beneficial effect of therapeutic nutritional interventions should be monitored not only via body weight, because this may be misleading in cases such as oedema formation, but also via the afore-mentioned serum surrogate parameters such as the course of serum albumin levels (taking into account the multiple differential diagnoses in the interpretation of the results) and via BIA measurements, which will likely represent the specific body compositional changes most precisely.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several RCTs and meta-analyses demonstrated that diarrhea was the most common adverse reaction in EGFRTKIs. 39,40 This type of diarrhea is thought to be primarily secretory; however, the mechanism still remains controversial. 41,42 Diarrhea can cause discomfort, fatigue, sleep disturbance, and can affect social function.…”
Section: Discussionmentioning
confidence: 98%